Edutainment (Edukasi dan Entertainment) Untuk Program Rehabilitasi dan Peningkatan Komitmen Anti-Narkoba di LRPPN Banyuwangi - Hikmah, Faiqatul; Kartika , Ria Chandra; Susindra , Yoswenita; Setyowati, Lisus; Satya, Malinda Capri Nurul; Khamid, M. Nur (SEJAGAT : Jurnal Pengabdian Masyarakat, 2025)
Drug abuse remains a serious public health issue, particularly in the rehabilitation process which demands high commitment from residents. This community service aimed to enhance the motivation and engagement of residents at the Banyuwangi Rehabilitation and Prevention Center (LRPPN) through an edutainment-based approach. Activities included educational games, arts, music, and the signing of an Integrity Pact. This method was tailored to the characteristics of residents who often exhibit low motivation, poor self-esteem, and limited social communication skills. The results indicated that edutainment was effective in creating a positive atmosphere, encouraging active participation, and fostering personal reflection and commitment to a drug-free life. Furthermore, this activity served as a valuable experiential learning opportunity for health promotion students to apply their skills directly in the field. This program is recommended as an alternative, humanistic, and participatory strategy to support successful rehabilitation outcomes.